2019
DOI: 10.1177/0363546518823337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pharmacological Therapies for Adhesive Capsulitis of the Shoulder: A Systematic Review and Network Meta-analysis

Abstract: Background: Several pharmacological interventions are used for the management of adhesive capsulitis of the shoulder, although the optimal treatment has yet to be defined. Purpose: To conduct a network meta-analysis to compare the effects of different pharmacological interventions for adhesive capsulitis, administered either alone or after distension of the shoulder capsule. Study Design: Network meta-analysis. Methods: The authors searched Scopus, PubMed, and the Cochrane Central Register of Controlled Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 63 publications
(64 reference statements)
0
26
0
4
Order By: Relevance
“…The ideal number of glenohumeral corticosteroid injections for patients with adhesive capsulitis has not been well described. 8,19 A previous systematic review attempted to report on the benefit of multiple GH injections in patients with adhesive capsulitis. 19 Unfortunately, many of the included studies in this systematic review did not differentiate among one, two, and three injections but rather gave ranges for the number of injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal number of glenohumeral corticosteroid injections for patients with adhesive capsulitis has not been well described. 8,19 A previous systematic review attempted to report on the benefit of multiple GH injections in patients with adhesive capsulitis. 19 Unfortunately, many of the included studies in this systematic review did not differentiate among one, two, and three injections but rather gave ranges for the number of injections.…”
Section: Discussionmentioning
confidence: 99%
“…Intraarticular corticosteroid injections have been shown to be effective in treating adhesive capsulitis, with improvements in pain and range of motion (ROM), whereas treatment with oral antiinflammatory medications has not generally produced effective results. 7,8 Glenohumeral hydrodilation has shown mixed results and as such is typically not a routine part of the treatment algorithm for adhesive capsulitis. 9,10 Because adhesive capsulitis often resolves without surgical intervention, a prolonged course of nonoperative management is offered in an attempt to avoid surgical intervention.…”
mentioning
confidence: 99%
“…In shoulder pathologies such as FS or rotator cuff disease, intra-articular or periarticular corticosteroid injection is a method of choice among physicians because it rapidly reduces inflammation around the lesion in comparison with oral administration of corticosteroids and particularly acts locally, resulting in less severe systemic adverse effects. 24,25 In contrast to the expectation that a corticosteroid injection is locally acting, the corticosteroid is rapidly absorbed into the synovium after injection and thereafter induces systemic effects. 26,27 Moreover, several studies showed no significant difference in the improvement of shoulder pain between systemic corticosteroid injection and local corticosteroid injection; this occurred because the corticosteroid exerts its effect systemically rather than locally.…”
Section: Discussionmentioning
confidence: 99%
“…When treated conservatively, persistent pain and RC arthropathy may develop. On the contrary, arthroscopic repair under tension yields disappointing results with a rate of structural failures of up to 94% [2,3]. Several surgical techniques have been proposed depending on the patients' age and the occurrence of accompanying arthritis [1].…”
Section: Introductionmentioning
confidence: 99%